Time-varying risk aversion and inflation-consumption correlation in an equilibrium term structure model - Tilman Bletzinger; Wolfgang Lemke; Jean-Paul Renne (European Central Bank (ECB), 2025)
Inflation risk premiums tend to be positive in an economy mainly hit by supply shocks, and negative if demand shocks dominate. Risk premiums also fluctuate with risk aversion. We shed light on this nexus in a linear-quadratic equilibrium macrofinance model featuring time variation in inflation-consumption correlation and risk aversion. We obtain analytical solutions for real and nominal yield curves and for risk premiums. While changes in the inflation-consumption correlation drive nominal yields, changes in risk aversion drive real yields and act as amplifier on nominal yields. Combining a trend-cycle specification of real consumption with hysteresis effects generates an upward-sloping real yield curve. Estimating the model on US data from 1961 to 2019 confirms substantial time variation in inflation risk premiums: distinctly positive in the earlier part of our sample, especially during the 1980s, and turning negative with the onset of the new millennium.
Keywords: E43; E44; C32; 330; Term structure model; inflation risk premiums; demand and supply; risk aversion